DEVELOPMENT OF INTERACTIVE MATHEMATICS LEARNING MEDIA FOR SOCIAL ARITHMETICS MATERIALS WITH A CONTEXTUAL APPROACH BASED ON ADOBE FLASH - Siregar, Melia Shafira (Journal of Innovation in Research, Education and Culture (JIREC), 2025)
This study is a development research that produces a product in the form of mathematics learning media using Adobe Flash CS6, focusing on social arithmetic material for Grade VII. The researchers employed the 4D model (Define, Design, Develop, and Disseminate). The instruments used included: (1) a media expert evaluation questionnaire, (2) a material expert evaluation questionnaire, and (3) a student response questionnaire. The trial subjects consisted of 23 Grade VII students from Muhammadiyah 57 Medan Junior High School.The results of the study are as follows: (1) the development of mathematics learning media using Adobe Flash CS6 for social arithmetic material, and (2) the quality of the learning media based on validity aspects. From the material experts, the validation scores were 4.3 and 4.8, with an average of 4.5, categorized as “Very Good.” The average validation score from media experts was 4.7, also categorized as “Very Good.” Meanwhile, the student response score was 3.9, likewise in the “Very Good” category.   Based on these findings, the mathematics learning media developed using Adobe Flash CS6 on social arithmetic material is highly suitable for use as a reference teaching resource in the learning process.    Keywords: Learning Media Development, Social Arithmetic, Adobe Flash